2021
DOI: 10.3390/children8100857
|View full text |Cite
|
Sign up to set email alerts
|

Forced Oscillation Technique for Monitoring the Respiratory Status of Children with Cystic Fibrosis: A Systematic Review

Abstract: Spirometry is considered the gold standard method for monitoring lung function of patients with cystic fibrosis (CF) but it requires patients’ cooperation and therefore it is not useful for the majority of preschool-aged children. Oscillometry is an alternative modality for lung function monitoring that requires minimal cooperation and can be applied in children as young as 3 years of age. Furthermore, it generates lesser aerosol compared to spirometry, an issue that is of considerable importance in the COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…It has also been shown that spirometry may not be very sensitive in detecting mild to moderate lung damage in children with CF (5). What is more, during spirometry, a quite large amount of aerosol is generated, which is essential in the coronavirus disease 2019 era (6). Hence, there is a need for a lung function test that is sensitive enough to pick up early abnormalities and that can also be performed easily in preschool children and children with advanced bronchopulmonary disease, who are unable to perform spirometry (4).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has also been shown that spirometry may not be very sensitive in detecting mild to moderate lung damage in children with CF (5). What is more, during spirometry, a quite large amount of aerosol is generated, which is essential in the coronavirus disease 2019 era (6). Hence, there is a need for a lung function test that is sensitive enough to pick up early abnormalities and that can also be performed easily in preschool children and children with advanced bronchopulmonary disease, who are unable to perform spirometry (4).…”
Section: Introductionmentioning
confidence: 99%
“…It reflects the elasticity of the lung and is negative in sign. Other important parameters in IOS are frequency at which the reactance crosses zero is called resonant frequency (Fres) and AX, which represents the sum of all reactance components at all frequencies before the resonant frequency (6,9). IOS can differentiate between small and large airway obstruction and is more sensitive than spirometry for peripheral airway disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cystic fibrosis (CF) is a common autosomal recessive disorder, caused by cystic fibrosis transmembrane conductance regulator (CFTR) gene mutations, with highest prevalence in Europe, North America and Australia, affecting about 1 in 2000–3000 Caucasian population newborns [ 1 2 ]. CF morbidity and mortality is mainly attributed to lung disease progression and respiratory exacerbations [ 3 ]. CFTR protein is not just a chloride channel and its disfunction is at the base of a multisystem disease [ 4 5 ].…”
Section: Introductionmentioning
confidence: 99%